Cyst formation in the subchondral bone following cartilage repair - Gao, Liang (Clin Transl Med, 2020)
Subchondral bone cysts represent an early postoperative sign associated with many articular cartilage repair procedures. They may be defined as an abnormal cavity within the subchondral bone in close proximity of a treated cartilage defect with a possible communication to the joint cavity in the absence of osteoarthritis. Two synergistic mechanisms of subchondral cyst formation, the theory of internal upregulation of local proinflammatory factors, and the external hydraulic theory, are proposed to explain their occurrence. This review describes subchondral bone cysts in the context of articular cartilage repair to improve investigations of these pathological changes. It summarizes their epidemiology in both preclinical and clinical settings with a focus on individual cartilage repair procedures, examines an algorithm for subchondral bone analysis, elaborates on the underlying mechanism of subchondral cyst formation, and condenses the clinical implications and perspectives on subchondral bone cyst formation in cartilage repair.